Implementation Of Pretrial In Indonesia's Positive Legal Spatial As A Strengthening Of The Integrity Of The Criminal Justice System - Nurul Azmi, A.; Nurtresna, Robby; Agustin, Mela (Gayaku Publisher, 2022)
KUHAP explicitly explains that the process of implementing the law is part of the core instruments of law enforcement, such as the police apparatus, prosecutors and judiciary. A new step for procedural law, namely pre-trial in the Criminal Procedure Code, which is an innovation in Indonesian positive law. The trial at the first level is an innovation (new institution) of the KUHAP. Pretrial as one of the jurisdictions of the court horizontally or the application of coercive measures by the Police and the Attorney General's Office. The Constitutional Court (MK) in its decision Number 21/PUU-XII/2014 has determined a new pretrial object, namely the legal or illegal determination of the suspect, confiscation and search. The research method aims to explain how research is conducted to obtain maximum results. In this study, the authors used normative and empirical legal research methods. In Indonesia, the judiciary was born from the spirit of wanting to adopt the habeas corpus concept into the Criminal Procedure Code (KUHAP). This concept is presented to verify and test the coercive actions of law enforcement officials, both in the form of arrests and detentions. This is because these actions violate individual rights and freedoms. Therefore, a trial court process is necessary. Pretrial as a horizontal legal system between law enforcement officers. That the District Court has the authority to consider and decide according to the provisions stipulated by law. The main pretrial request according to Indonesian positive law has been poured into the Criminal Procedure Code in Article 1 number 10 in conjunction with Article 70. In the Criminal Procedure Code Articles 77-83 Chapter X part one has included pretrial and its rules.